Adopting an enterprise resource planning system in a privatized government unit: challenges and impacts - Zainol, Zaini; Hamdan, Hamdino (2011)
This study investigates the implementation of an enterprise resource planning (ERP) system in one of the government’s privatised unit, that specialises in printing. We focused on the implementation issues and impact of ERP’s adoption on the company's operation and labour’s productivity. The study used a case study approach and an interview was held with the general manager in-charged on corporate affairs. Findings revealed that, the implementation of its ERP system named, PRONTO received mixed reactions from employees. The more senior employees, who opted to be employed with the new company after privatisation, were found to be resistance towards PRONTO system. Other than that, there were also other challenges faced by the company during the implementation. However, in terms of labour’s productivity, the study found that after three years of ERP’s adoption, labour productivity had increased by 37.7 percent. Operationally, the study recorded some benefits from PRONTO implementation and are discussed further in the paper.